Bioactive ECM-mimicking nerve guidance conduit for enhancing peripheral nerve repair - Shuang Liu; Julia Simińska-Stanny; Lizhao Yan; Lihong Fan; Xiaoyue Ding; Tengda Ma; Wei Guo; Yingsong Zhao; Ming Li; Jianghai Chen; Oseweuba Valentine Okoro; Armin Shavandi; et al. (Materials Today Bio)
Extensive research efforts are being directed towards identifying alternatives to autografts for the treatment of peripheral nerve injuries (PNIs) with engineered nerve conduits (NGCs) identified as having potential for PNI patients. These NGCs, however, may not fulfill the necessary criteria for a successful transplant, such as sufficient mechanical structural support and functionalization. To address the aforementioned limitations of NGCs, the present investigation explored the development of double cross-linked hydrogels (o-CSMA-E) that integrate the biocompatibility of porcine tendon extracellular matrix (ECM) with the antimicrobial and conductive properties of methacrylated quaternary chitosan. The hydrogels had matrices that could promote the growth of axons and the transmission of neural signals. The hydrogels were subsequently incorporated into a nanofibrous PLLA-ZnO sheath scaffold (ZnO@PLLA) to emulate the natural nerve structure, guiding cell growth and facilitating nerve regeneration. The collaboration of core and sheath materials in ZnO@PLLA/o-CSMA-E nerve guidance conduits resulted in enhanced migration of Schwann cells, formation of myelin sheaths, and improved locomotion performance in rats with sciatic nerve defects when in vivo studies were undertaken. Notably, the in vivo studies demonstrated the similarity between the newly developed engineered NGCs and autologous transplants, with the newly engineered NGCs possessing the potential to promote functional recovery by mimicking the tubular structure and ECM of nerves.